The impact of linked color imaging on adenoma detection rate in colonoscopy: a systematic review and meta-analysis - Bruna Haueisen Figueiredo Zwetkoff; Luiz Ronaldo Alberti; Fábio Gontijo Rodrigues; Nelson Carvas Junior; José Celso Ardengh; Otavio Micelli Neto; Fernando Rodrigues Guzman; Marcelo Morganti Ferreira Dias; Guilherme Camarotti de Oliveira Canejo; Carlos Eduardo Oliveira dos Santos (Clinical Endoscopy)
Background/Aims Colorectal cancer prevention relies on surveillance colonoscopy, with the adenoma detection rate as a key factor in examination quality. Linked color imaging (LCI) enhances lesion contrast and improves the examination performance. This systematic review and meta-analysis aimed to evaluate the effect of LCI on adenoma detection rate in adults who underwent colonoscopy. Methods We searched the Medline, PubMed, BIREME, LILACS, and Scientific Electronic Library Online databases for randomized controlled trials comparing the use of LCI versus white light imaging (WLI), published up to March 2023. The outcomes included lesion characteristics, number of adenomas per patient, and the additional polyp detection rate. Results Sixteen studies were included in the analysis, which showed that LCI was more accurate than WLI in detecting adenomas, with an increased number of adenomas detected per patient. Although LCI performed well in terms of lesion size, morphology, and location, the subgroup analyses did not reveal any statistically significant differences between LCI and WLI. The addition of LCI did not result in significant improvements in the detection of serrated lesions, and there were no differences in the withdrawal time between groups. Conclusions LCI has been shown to be effective in detecting colonic lesions, improving the number of adenomas detected per patient and improving polyp detection rate without negatively affecting other quality criteria in colonoscopy.